Ajuste de la curva logistica aplicada en los datos censales de la poblacion peruana 1836-2007 - Cruz Ipanaqué, Brisset Melissa (2015)
Ajuste de la curva logistica aplicada en los datos censales de la poblacion peruana 1836-2007